Al-Qur’an dan Misteri Singularitas Awal: Telaah Tafsir Tematik Ayat-Ayat Kosmologis - Lulu Qutratu’aina (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2025)
This research examines the mystery of the initial singularity of the universe—a central concept in the Big Bang theory—through a thematic analysis of cosmological verses in the Qur’an. The Big Bang theory states that the universe originated from an infinitely dense singularity but does not explain the conditions